Keingesan Kembang Pesisi: Pembaruan Etnik Budaya Dan Moderenisasi Melalui Fashion Design - Nurfadila, Rahma Nisa; Prahastuti, Endang; Kusumawardani, Hapsari; Nafiah, Annisau (Institut Seni Indonesia Yogyakarta, 2024)
This article explores the creation of a fashion work themed